Modelling multi-scale problems in the transmission line modelling method - Meng, Xuesong (2014)
Modern electromagnetic problems are becoming increasingly complex and their simulation must take into account geometrical features that are both large and small compared to the wavelength of interest. These multi-scale problems lead to a heavy computational burden in a discretised computational simulation approach since the small features require fine mesh to be used in the simulation, resulting in large run time and memory storage. To overcome such problems, this thesis presents an efficient and versatile method for embedding small features into an otherwise coarse mesh. The embedded model eliminates the need for discretising the small features and allows for a relative large mesh size to be used, thus saving the computational costs.